The retail brand personality—Behavioral outcomes framework: Applications to identity and social identity theories - Kuo, Ya-Hui (Frontiers in Psychology, 2022)
This study applies identity and social identity theories to develop and test a framework in which retail brand personality influences consumer outcomes (i.e., positive WOM about and patronage intention toward the retailer) through public and/or private self-congruity, strengthened by shopping conspicuousness situation, and retail brand identification (RBI). This is the first paper to include social shopping situations to study brand personality and self-congruity. A questionnaire with a 2 (retailer image format) × 2 (shopping situation conspicuousness) between-subjects design was conducted on a sample of US consumers. Structural equation modeling was used to test the hypotheses. The findings suggest a framework in which Genuine, the most influential dimension of retail brand personality, predicted outcome behaviors both directly and indirectly through self-congruities and RBI. The high shopping conspicuousness situation strengthened the relationship between public self-congruity and overall RBI. The concept of RBI provides an additional theoretical perspective for guiding future research on shopper-brand relationships. In addition, this framework provides practical implications for retail environment design and customer-brand relationship management.